1999
DOI: 10.1093/humrep/14.10.2474
|View full text |Cite
|
Sign up to set email alerts
|

Conventional in-vitro fertilization versus intracytoplasmic sperm injection in sibling oocytes from couples with tubal infertility and normozoospermic semen

Abstract: An auto-controlled study was conducted in couples with tubal infertility and normozoospermic semen. The fertilization rates and embryonic development in sibling oocytes treated, using the same semen sample, either by conventional in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) at the same time were compared. Sibling oocyte-cumulus complexes (OCC) of 56 different couples with tubal infertility and normozoospermic semen were randomly divided in order of retrieval into two groups inseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 26 publications
4
63
1
3
Order By: Relevance
“…Hence, micromanipulation technique appears to have no negative effect on the embryonic development. These results are in view of previous studies, which found no differences in the embryo development in sibling oocytes regardless of the fertilization procedure [23,37].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hence, micromanipulation technique appears to have no negative effect on the embryonic development. These results are in view of previous studies, which found no differences in the embryo development in sibling oocytes regardless of the fertilization procedure [23,37].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, a comparison between embryo transfer cycles in which either ICSI only or IVF only embryos were transferred revealed no statistically significant differences in pregnancy rate, implantation rate or pregnancy outcome. Previous studies found similar fertilization rates of sibling oocytes inseminated by either ICSI or conventional IVF in couples with tubal infertility and normozoospermic semen [23][24][25]. In contrast, in the current study we found a significantly higher fertilization rate of oocytes inseminated by ICSI as compared to conventional IVF.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…ICSI is powerful for treating male-factor infertility that could not be assisted using conventional IVF. However, unexpected fertilization failures from IVF in couples with normal semen may occasionally occur (14,15). There are no absolute parameters or sperm function tests to predict fertilization outcome for apparently normal semen.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators attempted IVF-ICSI split on fresh sibling oocytes as the insemination method for normal semen to prevent fertilization failures (14,15). For couples with tubal or unexplained infertility, they found that the use of ICSI rescued 9-16% of cycles where IVF failed.…”
Section: Discussionmentioning
confidence: 99%